Audio-Visual Learning Technology Improves Basketball Dribbling Skills In Third Grade Elementary School Students - Risa Agus Teguh Wibowo; Muchamad Sholeh; Christoper Bambang A; Nesa Catrin Pratiwi (LITERACY : International Scientific Journals of Social, Education, Humanities, 2026)
Physical education in elementary schools plays a crucial role in developing students' basic motor skills, including dribbling in basketball. However, conventional teaching methods often hinder the achievement of optimal learning outcomes. This study aims to analyse the effect of implementing audiovisual learning technology on students' learning outcomes in basic basketball dribbling skills among third-grade elementary students. The research employed a quantitative approach with a quasi-experimental design involving two groups: the experimental group (using audiovisual media) and the control group (using conventional methods), each consisting of 24 students. The instruments used included a basketball dribbling skill test and a learning activity observation sheet. Data analysis using paired sample t-test and independent sample t-test was conducted. The analysis revealed a significant difference in learning outcomes between students taught with audiovisual media and those taught with conventional methods (p < 0.05). The experimental group showed a significantly higher improvement in learning outcomes. These findings affirm that audiovisual technology can provide a more interactive and effective learning experience, particularly in motor skill development. This study recommends the integration of audiovisual media into physical education strategies to better meet the contextual needs of digital-native learners, highlighting the innovative use of audiovisual technology as a more effective tool in motor skill education compared to conventional teaching methods.